Empirical tests on the Hungarian stock market efficiency: economic value of stock return forecasts - Csuthi, Virág (2021)
This paper focuses on the Hungarian stock market efficiency by applying a customized version of the recursive modeling approach and the switching portfolio strategy employed by Pesaran and Timmermann (1995). I investigate whether this modeling technique could have been more profitable comparing to a passive investment. I discover that the variables’ predictive power and the economic value of the forecasts are liable to changes during the examined timeframe and the switching trading strategy cannot beat the market in the full sample. It provides approximately 1.5 times higher wealth, than the portfolios under the different model selection criterions. However, splitting the sample into two, the economic value of the forecasts becomes significant and the switching strategy can result economic profit.